Kazakhstan as a country with a high share of the commodity sector in the context of «Green Growth» (Journal of Geography and Environmental Management, 2019)
The article analyzes the state and possibility of Kazakhstan’s transition to the green economy. The republic as an adherent to sustainable development is making efforts to transform gradually the «brown economy» into the «green» one. The «green economy» is an instrument leading to the economy aimed at improving human well-being and creates favorable quality conditions for development of future generations and a careful attitude to natural resources. Development of the «green» economy will allow Kazakhstan to avoid the ecological crisis, which has already affected many post-industrial countries by its scale. The authors analyze the energy status of Kazakhstan, where coal remains the main fuel and energy resource, as well as the energy intensity of Kazakhstan’s GDP based on statistical data. The study considers potential and possibility of developing the green energy in the country. The ways of transformation can be differentiated depending on not only the economic development of the country, but also on the social situation as well as development of social relations. Applying the methods of multidimensional statistical analysis, the authors established criteria in relation to the global indicators, which allow determining the place of the country in the world. Based on this criterion, the study calculates the share of investmentsthat need to transform economy for some developed and developing countries.